2013
DOI: 10.1039/c3ta00107e
|View full text |Cite
|
Sign up to set email alerts
|

DNA: a novel, green, natural flame retardant and suppressant for cotton

Abstract: For the first time, deoxyribonucleic acid (DNA) from herring sperm has been employed as a novel flame retardant system for enhancing the thermal stability and flame retardant properties of cotton fabrics.Indeed, DNA could be considered an intrinsically intumescent flame retardant as it contains the three main components that are usually present in an intumescent formulation, namely: the phosphate groups, able to produce phosphoric acid, the deoxyribose units acting as a carbon source and blowing agents (upon h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
131
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 279 publications
(134 citation statements)
references
References 23 publications
(23 reference statements)
2
131
0
1
Order By: Relevance
“…Similarly to other biomacromolecules, the presence of the coating strongly anticipated the cellulose decomposition, which was directly related to the DNA add-on: in particular, as assessed by TG analyses in nitrogen and air, the higher was the biomacromolecule add-on, the lower was the temperature, at which degradation started to occur. This finding was attributed to the phosphate groups of the biomacromolecule, which decompose at about 200 • C, releasing phosphoric acid, hence favoring the dehydration of the fabrics, and finally giving rise to the formation of a residue, thermally stable up to 500-600 • C [73,83]. Flammability tests performed in horizontal configuration clearly demonstrated that the self-extinction of the treated fabrics strictly depends on the biomacromolecule add-on: in particular, the fabrics having the lowest DNA add-on (i.e., 5 wt %) burnt completely, while the other specimens (having 10 or 19 wt % add-on) were able to achieve the flame out.…”
Section: Deoxyribonucleic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to other biomacromolecules, the presence of the coating strongly anticipated the cellulose decomposition, which was directly related to the DNA add-on: in particular, as assessed by TG analyses in nitrogen and air, the higher was the biomacromolecule add-on, the lower was the temperature, at which degradation started to occur. This finding was attributed to the phosphate groups of the biomacromolecule, which decompose at about 200 • C, releasing phosphoric acid, hence favoring the dehydration of the fabrics, and finally giving rise to the formation of a residue, thermally stable up to 500-600 • C [73,83]. Flammability tests performed in horizontal configuration clearly demonstrated that the self-extinction of the treated fabrics strictly depends on the biomacromolecule add-on: in particular, the fabrics having the lowest DNA add-on (i.e., 5 wt %) burnt completely, while the other specimens (having 10 or 19 wt % add-on) were able to achieve the flame out.…”
Section: Deoxyribonucleic Acidmentioning
confidence: 99%
“…The structure of the obtained LbL assembly is schematized in Figure 30. biomacromolecule, which decompose at about 200 °C, releasing phosphoric acid, hence favoring the dehydration of the fabrics, and finally giving rise to the formation of a residue, thermally stable up to 500-600 °C [73,83]. Flammability tests performed in horizontal configuration clearly demonstrated that the self-extinction of the treated fabrics strictly depends on the biomacromolecule add-on: in particular, the fabrics having the lowest DNA add-on (i.e.…”
Section: Deoxyribonucleic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, in previous reports, we have clearly demonstrated that this biomacromolecule is very effective in conferring flame retardant features to cellulosics [13,14]. In particular, in the first pioneering work [13]we have proved that the only application of low molecular size DNA from herring sperm to cotton fabrics (with a final 19 wt.-% dry add-on) by an impregnation/exhaustion method allows enhancing the thermal stability and flame retardant properties of cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the first pioneering work [13]we have proved that the only application of low molecular size DNA from herring sperm to cotton fabrics (with a final 19 wt.-% dry add-on) by an impregnation/exhaustion method allows enhancing the thermal stability and flame retardant properties of cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%